Kemampuan Pemecahan Masalah pada Materi Pecahan Siswa Kelas IV SD YPK ELIM MALANU Kota Sorong - Theresa Oraple; Anis Alfian Fitriani; Ahmad Yulianto (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research is inspired by the lack of students' ability to solve math problems, especially in fraction material. This can be seen from the results of the daily test of fraction material which is still under the Minimum Completeness Criteria (KKM). The purpose of this study was to determine whether there is an effect of the inquiry learning model on students' mathematical problem solving ability on fraction material in Class IV of YPK Elim Malanu Elementary School in Sorong City. This research is quantitative research using experimental methods. The data collecting techniques that were used were observation, test, and documentation techniques. The instrument used in this research is a test, which is divided into pre-test and post-test. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of descriptive analysis showed that the average learning outcomes of mathematics that were taught using the inquiry learning model from 47.78 became 73.77. Furthermore, the results of inferential analysis using SPSS show that there is a significant difference between the learning outcomes of mathematics that were taught using the inquiry model. The calculation result of sig value = 0.98 is less than a = 0.05 (0.98 < 0.05) which means Ho is rejected and Ha is accepted.